Study of Calcium, Magnesium and Phosphorus Levels among Hypothyroid Patients in Trichy, Tamil Nadu - M, Rasheed Khan; A.G, Thivyah Prabha; K, Siva Kumar (Journal of evidence based medicine and healthcare, 2021)
BACKGROUND Mineral metabolism is frequently disturbed in thyroid dysfunctions. Among thyroid dysfunctions, hypothyroidism is one of the most common form resulting from the deficiency of thyroid hormones. Studies done on serum calcium, phosphorus and magnesium in hypothyroid patients earlier have conflicting results. Hence the present study has been undertaken to study the levels of serum calcium, phosphorus, and magnesium among hypothyroid patients and analyse their correlation with thyroid stimulating hormone (TSH). METHODS The case control study was conducted in the Department of Biochemistry in Trichy SRM Medical College Hospital and Research Centre for a period of 6 months from 2017 January to July 2017. The study was undertaken involving 50 hypothyroid cases and 50 healthy volunteers as controls after proper ethical clearance and informed consent of all the study subjects. Serum calcium, phosphorus and magnesium were measured along with tri-iodothyronine (FT3), tetra-iodothyronine (FT4) and TSH among all study subjects. Statistical analysis of data was done using statistical package for social sciences (SPSS) software. RESULTS The mean value of serum total calcium and total magnesium was lower among hypothyroid cases and phosphorus value was increased as compared to controls. (P < 0.001) Statistically significant negative correlation was observed between serum calcium, magnesium and TSH among hypothyroid cases. Statistically significant positive correlation was observed between serum phosphorus and TSH among hypothyroid cases. CONCLUSIONS Among hypothyroid patients the values of serum calcium, magnesium and phosphorus is significantly altered. Thyroid disorders have an important role in bone and mineral metabolism. Thus, monitoring of these minerals among hypothyroid patients in regular follow up may effectively improve the clinical manifestations in them. Hence, monitoring of mineral status of the hypothyroid patients on follow-up will be of benefit to the patients. KEYWORDS Hypothyroidism, Calcium, Phosphorus, Magnesium, Minerals